Prevalence of nonalcoholic fatty liver disease in an adult population in a rural community of Haryana, India - Anindo Majumdar; Puneet Misra; Sanjay Sharma; Shashi Kant; Anand Krishnan; Chandrakant S Pandav (Wolters Kluwer Medknow Publications, 2016)
Background: Though nonalcoholic fatty liver disease (NAFLD) is increasingly becoming prevalent in the Indian population, knowledge regarding the burden and risk factors of NAFLD is limited, more so from rural areas. This study was thus conducted to estimate the prevalence of NAFLD among adults in a rural community of Haryana, India and to measure the association of diet, physical activity, and other selected risk factors with NAFLD. Materials and Methods: The present study was conducted in a rural community of Haryana, India among resident adults ≥35 years of age. Eight out of 28 villages were selected by probability proportion to size sampling. The number of eligible and consenting participants randomly selected from each village was 27. Out of 216 participants thus recruited, 184 participants reported for undergoing ultrasonography (USG) of the liver, anthropometry, blood pressure recording, and blood sample collection. Finally, 176 participants were analyzed. Results: Prevalence of NAFLD was 30.7%. There was no significant difference in the calorie intake and average total physical activity between participants with and without NAFLD. On multivariate analysis, hypertension [adjusted odds ratio (OR): 2.3, 95% confidence interval (CI): 1.1-5.0, P 0.03] and an increased waist circumference (adjusted OR: 4.9, 95% CI: 1.5-7.0, P < 0.001) were independently associated with NAFLD. A normal high-density lipoprotein (HDL) level was protective against NAFLD (adjusted OR: 0.4, 95% CI: 0.2-0.8, P 0.001). Conclusions: The high prevalence of NAFLD is already a public health problem, even in the rural parts of India. Urgent public health interventions are required to prevent its development by controlling the cardiometabolic risk factors associated with it.